REALIZATION AS THE BASIS FOR ASSET CLASSIFICATION AND MEASUREMENT. - Mauriello, Joseph A. (The Accounting Review, 1963)
In this article, the basic characteristics of assets are examined for the purpose of arriving at meaningful balance sheet groupings and appropriate valuations of the classified items. Such a study and approach results in a unitary principle for classification and valuation. It is concluded that regarding (last in first out) LIFO, the principle of cash realizable value requires, as a minimum, footnote disclosure of the higher cash realizable value, with an indication of the estimated income tax applicable to the excess of cash realizable value over LIFO cost, payable at such times as the inventory increment is realized. The principle requires, as a maximum, that the body of the balance sheet reflect (1) an adjustment of LIFO cost to the higher cash realizable value, (2) a long-term tax liability for the estimated income taxes applicable to the inventory adjustment, and (3) a special retained earnings component for the difference between the inventory increase and the related tax.